The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.14689/ejer.2017.72.11
|View full text |Cite
|
Sign up to set email alerts
|

Science Teacher Candidates’ Epistemological Beliefs and Critical Thinking Disposition

Abstract: The purpose of the study is to determine the effect of gender and class level on science teacher candidates' epistemological beliefs and critical thinking disposition, as well as examine the relationship between these two dependent variables.Research Methods: This study was designed as a descriptive survey. Participants were 447 students majoring in science education. The data for the epistemological beliefs was collected with the Scale of Epistemological Beliefs (SEB); data for critical thinking disposition w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 209 publications
1
4
0
Order By: Relevance
“…Accordingly, it was determined that there are low and medium level significant relationships between the access to knowledge and simple knowledge dimensions of the epistemological belief scale and the reasoning and reaching a judgment dimensions of critical thinking. Similar to the findings of this study, significant relationships between epistemological beliefs and some dimensions of critical thinking are found in the research results in the literature (Basbay, 2013;Chan et al 2011;Hofer, 2004;Kandemir and Egmir, 2020;Koyunlu Unlu and Dokme, 2017;Sivgin, 2019). Chan et al (2011) determined that there is an important link between naive epistemological beliefs and weak critical thinking disposition.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…Accordingly, it was determined that there are low and medium level significant relationships between the access to knowledge and simple knowledge dimensions of the epistemological belief scale and the reasoning and reaching a judgment dimensions of critical thinking. Similar to the findings of this study, significant relationships between epistemological beliefs and some dimensions of critical thinking are found in the research results in the literature (Basbay, 2013;Chan et al 2011;Hofer, 2004;Kandemir and Egmir, 2020;Koyunlu Unlu and Dokme, 2017;Sivgin, 2019). Chan et al (2011) determined that there is an important link between naive epistemological beliefs and weak critical thinking disposition.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…Active learning emphasizes practicing and creating knowledge from what a person is practicing while working [16]. Active learning focuses on developing skills and competencies under the former knowledge bases that affect the learners to connect new knowledge with the previous ones received from practice and practitioners' needs mainly [17,18]. Hence, the results of those becoming successful executives would have an absolutely positive impact on the organization.…”
Section: • Active Learningmentioning
confidence: 99%
“…Research has also shown that, compared to less constructivist epistemic cognition, more constructivist epistemic cognition has been related to the will to take on multiple perspectives, reconsider one's own thinking when drawing conclusions about controversial issues (Schommer-Aikins and Hutter, 2002), engage in effortful thinking (Hyytinen et al, 2014), and display skepticism toward unreliable sources (McGinnis, 2016). Though motivational and affective dispositions have theoretically been proposed to support critical thinking within the epistemic cognition literature (Chinn et al, 2011;Muis et al, 2015Muis et al, , 2018, little research has been conducted to understand how epistemic cognition relates to the affective states that dispose learners to think critically.…”
Section: Relations Between Epistemic Cognition and Critical Thinkingmentioning
confidence: 99%